Capital Structure and Investment Return: A Case Study of PT Semen Indonesia - Riska; Neneng Yanti Andriani (PT. Gudang Pustaka Cendekia, 2025)
This study aims to analyze the effect of Debt to Asset Ratio (DAR) and Long Term Debt to Equity Ratio (LTDTER) on Return on Investment (ROI) at PT Semen Indonesia (Persero) Tbk during the period 2016–2023. The method used is descriptive associative with a quantitative approach, using secondary data in the form of the company's quarterly financial reports obtained through purposive sampling techniques. The analytical tools used include Pearson Product Moment correlation analysis, coefficient of determination (R²), t-test and F-test, and multiple linear regression. The results of the study show that DAR has a negative correlation with ROI of -0.607, while LTDTER also shows a negative correlation of -0.478, both of which are included in the weak relationship category. The coefficient of determination value of 50.4% indicates that half of the variation in ROI can be explained by the two independent variables, while the remaining 49.6% is influenced by other factors outside the study. The F test shows that DAR and LTDTER simultaneously have a significant effect on ROI. This finding confirms that a high debt-based capital structure has a negative impact on investment returns, making it important for financial management to consider the efficiency of long-term debt use and total debt in long-term financial strategies.